Weather - Clarke, Catriona; Chen, Kuo Kang (London Scholastic, 2020)
What makes the wind blow? How can rain sometimes be red? Why are tornadoes like vacuum cleaners? You'll find out the answers and lots more about weird and wonderful weather in this fascinating book. Usborne Beginners are colourful information books for children beginning to read on their own.
Grade 4
eng